2012
DOI: 10.3390/app2020513
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Amphiphilic Composites Applied for the Treatment of Biodiesel Wastewaters

Abstract: In this work, new magnetic amphiphilic composites were prepared by chemical vapor deposition with ethanol on the surface of hydrophilic natural chrysotile matrix containing Fe catalyst. XRD, Raman, Mössbauer and SEM analyses suggest the formation of a complex nanostructured material composed of hydrophobic carbon nanotubes/nanofibers grown on the hydrophilic surface of the MgSi fiber mineral and the presence of Fe metallic nanoparticles coated by carbon. These nanostructured particles show amphiphilic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
0
13
0
1
Order By: Relevance
“…In further recycling tests, the M-EC was found to remain effective in demulsifying water in diluted bitumen emulsions after up to 10 times reuse by magnetic separation and solvent washing. 469 Interestingly, this novel concept of magnetic nanoparticle-based demulsifiers has been further developed for the synthesis of other novel demulsifiers, such as magnetic poly(methylmethacrylate-acrylic acid-divinylbenzene) iron oxide (P(MMA-AA-DVB)/Fe 3 O 4 ) Janus particles, 470 nanostructured magnetic amphiphilic composites, 471 and single-layer oleic acid-coated magnetite (Fe 3 O 4 @OA) nanoparticles. 472 4.4.4 Electric field enhanced demulsification.…”
Section: Demulsification Of Heavy Oil Emulsionsmentioning
confidence: 99%
“…In further recycling tests, the M-EC was found to remain effective in demulsifying water in diluted bitumen emulsions after up to 10 times reuse by magnetic separation and solvent washing. 469 Interestingly, this novel concept of magnetic nanoparticle-based demulsifiers has been further developed for the synthesis of other novel demulsifiers, such as magnetic poly(methylmethacrylate-acrylic acid-divinylbenzene) iron oxide (P(MMA-AA-DVB)/Fe 3 O 4 ) Janus particles, 470 nanostructured magnetic amphiphilic composites, 471 and single-layer oleic acid-coated magnetite (Fe 3 O 4 @OA) nanoparticles. 472 4.4.4 Electric field enhanced demulsification.…”
Section: Demulsification Of Heavy Oil Emulsionsmentioning
confidence: 99%
“…Os espectros são formados pela superposição de um dupleto bem definido característico de Fe +3 paramagnético, estrutura de aluminossilicatos, ou a óxidos de ferro sob relaxação superparamagnética, como hematita e/ou goethita com tamanho médio de partículas muito pequeno [26]. O campo máximo obtido (B hf (max) = 50,41 T) é menor que o valor característico para a hematita, 51,8 T, o que, de acordo com Cornell e Schwertmann [27], é característico de materiais que apresentam substituição isomórfica de Fe 3+ por Al 3+ e devido ao pequeno tamanho de partícula da hematita [28,29]. Os valores dos parâmetros hiperfinos obtidos pelos ajustes do espectro são descritos na Tabela 2.…”
Section: Caracterizaçãounclassified
“…PAM (polyacrylamide), NaHCO 3 and CuSO 4 •5H 2 O were obtained from Alfa-Aesar. Commercial Fe/C ceramic-filler (CF, employed as comparison materials) and commercial lightweight-ceramic-filler (LCF, applied as filler for BAFs in pilot-scale test) which had been frequently utilized in our previous studies [24][25][26] were shown in Table 2. Table 2.…”
Section: The Tncs and Codcr Removal By Systemmentioning
confidence: 99%